Zwischen Wahlfreiheit und Entscheidungszwang: Zur Ökonomie des "entlastenden" Sterbens - Graefe, Stefanie (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2007)
The "Patientenverfugung" (advcance directive/living will) as well as the passive and indirect euthanasia is expected to be completely legalized in Germany. The patient’s "autonomy at the end of life" is a key concept in the contemporary debate. The law is expected to enable each individnal to enact the medical-assisted preterrn ending of one’s life - not only in case of approaching death, but also in all cases in which the patient is not able to express his or her will (e.g. vegetative state, dementia). On the one hand, normalizing the need for a living will activites social fears of becoming a "burden" to relatives or society in times of "limited resources." On the other hand it presents itself as an option to regulate and appease those fears. Such hidden links are analysed.